SEASONAL VARIABILITY IN PENAEID PRAWN LARVAL ABUNDANCE IN THE MANDOVI AND ZUARI ESTUARIES, GOA. - GOSWAMI, S. C.; GOSWAMI, USHA (Journal of Indian Fisheries Association, 2015)
Seasonal variations in the occurrence and abundance of penaeid prawn larvae in theMandovi and Zuari estuaries of Goa were studied. Larvae and postlarvae of commerciallyimportant species viz. Metapenaeus dobsoni (Miers),M.affinis (H.Milne Edwards). M. monoceros(Fabricius), Penaeus merguiensis de Man and Parapenaeopsis stylifera (H.Milne Edwards)were recorded in that order of abundance. Protozoea and mysis stages were dominant insurface zooplankton collections while the postlarvae were more in the bottom samples. Basedon larval density, M. dobsoni appeared to be a continuous breeder. The active spawning periodsin other species were during the late postmonsoon and premonsoon seasons varying with thespecies. Peak recruitment of postlarvae in the estuaries was observed mostly during southwestmonsoon months (June to September). Penaeid prawn larval ingression was more in the Zuariestuary compared to the Mandovi estuary. Their numerical abundance gradually decreasedtowards the upstream areas. The feasibility of large scale collection of penaeid prawn larvaefor aquaculture is indicated